PERKEMBANGAN MEDIA PENYIARAN TELEVISI : Menjadikan Televisi Sebagai Kebudayaan Masyarakat - DA, NRA. Candra (Capture : Jurnal Seni Media Rekam, 2010)
Television is one of the most widely broadcast media undergo a process of evolution. Today the presence of broadcast media is certainly not out of a myriad of appreciation from many in the community. Man himself was unable to deny that a television media will always be present in front of him. Various impressions broadcast program comes through this medium, different interpretation will emerge from the community as audience. Now, television has become an important need among the millions of people in the world community. This can happen because one characteristic of this form of broadcast media that is intrinsically capable explores some of the information occurs in parts of the world manapan the same time. As part of a development of new audio-visual culture, television becomes the thinking about the main attraction in an impact to thewider community . Positive and negative impacts of television media can only be known if the people themselves are willing and able to follow the development of this medium.Keywords: Broadcasting Media, TV Function, and Society